2012
DOI: 10.1002/ibd.21852
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin-producing staphylococci cause intestinal inflammation by a combination of direct epithelial cytopathy and superantigen-mediated T-cell activation

Abstract: Staphylococci induce enterocolitis by a combination of direct enterocyte cytopathy mediated by EDIN toxins, disrupting the epithelial barrier, and enterotoxin superantigen-induced mucosal T-cell activation. Gut epithelial production of β-defensins may contribute to host defense against invasive staphylococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…It has also been suggested that SAgs liberated in the gastrointestinal tract by food-borne pathogens may cross the perturbed gut mucosa either directly or with the assistance of other bacterial toxins [57,58] and consequently access the liver via the portal vein [12]. The abundance of MAIT cells in the intestine and in the liver inevitably puts them in a unique position to respond to SAgs with deleterious outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that SAgs liberated in the gastrointestinal tract by food-borne pathogens may cross the perturbed gut mucosa either directly or with the assistance of other bacterial toxins [57,58] and consequently access the liver via the portal vein [12]. The abundance of MAIT cells in the intestine and in the liver inevitably puts them in a unique position to respond to SAgs with deleterious outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of S. aureus can produce enterotoxins, capable of functioning as superantigens that activate large numbers of non-specific T-cells in the gut [14]. In vitro stimulation of peripheral blood mononuclear cells (PBMC) with superantigenic S. aureus and/or other toxins from staphylococci induces IL-17 production by T-cells [15,16], a cytokine highly associated with both allergy and autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, experts in both Europe and the USA have rekindled their interests in S. aureus as a potential cause for AAE [62,86-88]. It is also important to note that other pathogens such as Klebsiella oxytoca have also been found to cause AAE [15].…”
Section: Discussionmentioning
confidence: 99%